A methodology to restructure a pipeline system for an oilfield in the mid to late stages of development. (12th July 2018) - Wang, Bohong; Liang, Yongtu; Zheng, Jianqin; Lei, Tiantian; Yuan, Meng; Zhang, Haoran
Highlights: l An MINLP model for the restructuring of GPN in an oilfield is proposed. l Hydraulic constraints are considered in the model. l Three economic items are considered in the objective functions. l The piecewise linearization method is applied to the model. l A case of an oilfield in China is studied to show the effectiveness. Abstract: One important issue in the mid to late development stages of oilfields is maintaining stable production, especially when the existing gathering pipeline system cannot fully satisfy the development of low pressures and low production rates. In these cases, it is necessary to restructure the original gathering pipeline system. In this study, an optimal design method is proposed to restructure a pipeline system in an oilfield in the mid to late development stages. Based on the demand of stable production and the existing structure of the pipeline system, a mixed-integer nonlinear programming (MINLP) model with an objective function that minimizes the total cost is developed. Hydraulic, technical and economic constraints are considered. The model is linearized based on a piecewise method and solved by the branch-and-bound algorithm. This method is applied to a real case study of a pipeline system in an oilfield.